Designing successful post-retirement solutions by blending growth, income and protection ‐ Abstract of the Edinburgh Discussion. (13th March 2017) - Unknown
Abstract : This abstract relates to the following paper:L-A. Morgan andS.A. Lothian Designing successful post-retirement solutions by blending growth, income and protection.British Actuarial Journal, doi:10.1017/S1357321717000034